Secretome-Based Prediction of Three-Dimensional Hepatic Microtissue Physiological Relevance - Asthana, Amish; White, Charles M.; Ndyabawe, Kenneth; Douglass, Megan; Kisaalita, William S. (ACS Biomaterials Science & Engineering, 2019)
Early biomarkers for indication of the complex physiological relevance (CPR) of a three-dimensional (3D) tissue model are needed. CPR is detected late in culture and requires different analytical techniques. Albumin production, CYP3A4 expression, and formation of bile canaliculi structures are commonly used to compare in vitro hepatic cells to their in vivo counterpart. A universal biomarker independent of the cell type would bring this to a common detection platform. We make the case that these hepatic characteristics are not sufficient to differentiate traditional (2D) cell culture from the more complex 3D culture. We explored the cytokine secretion profile (secretome) for its potential as a 3D early culture biomarker. PDGF-AB/BB and vascular endothelial growth factor (VEGF) were found to be upregulated in 3D compared to 2D cultures at early time points (days 3 and 4). These observations provide a foundation upon which in vivo validation of cytokines can lead to physiologically relevant 3D in vitro cell culture.